Art collection study Light level, texture and color - Singson, Millicent Hernandez (2011)
The Jorge B. Vargas house different art collection such as oil paintings, watercolors, pastels, drawings, and sculptures. This theses focused on the permanent artworks on display in the Main Gallery of the Vargas Museum and on the artistic components of Fernando Amorsolo paintings, that is, texture and color.